2020
DOI: 10.1096/fj.201903160rr
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of cell stretch on keratin filaments in A549 lung cells

Abstract: The group of intermediate filaments (IFs) comprise numerous different subtypes with keratin filaments (KFs) being characteristic for epithelia. The functions of KFs vary from signaling to coping mechanisms for cell stress 1-3 and their mere abundance and big surface area 4 might facilitate even more, yet, unrecognized roles in the cell. However, KFs' classic role as stretch resistant mechanical stabilizers of the cell 2 remains keratin's most outstanding feature. KFs' tensile resistance is founded on a filamen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…2 B ). Consistent with previous studies ( Felder et al, 2008 ; Lutz et al, 2020 ), our quantitative analysis revealed that monolayer stretching led to a significant increase in the cross-sectional DSM width in both WT and KO monolayers ( Fig. 2 E ).…”
Section: Resultssupporting
confidence: 92%
“…2 B ). Consistent with previous studies ( Felder et al, 2008 ; Lutz et al, 2020 ), our quantitative analysis revealed that monolayer stretching led to a significant increase in the cross-sectional DSM width in both WT and KO monolayers ( Fig. 2 E ).…”
Section: Resultssupporting
confidence: 92%
“…Using Equation (1), those curves can be fitted to calculate the Young's modulus at each position. AFM has been used to study the mechanics of different cell types [114][115][116] and has helped in understanding the underlying processes in various diseases, including cancer [117,118].…”
Section: Active Cellular Force Probingmentioning
confidence: 99%
“…AFM has been used to study the mechanics of different cell types [ 114 , 115 , 116 ] and has helped in understanding the underlying processes in various diseases, including cancer [ 117 , 118 ].…”
Section: Cellular Force Measurementmentioning
confidence: 99%
“…The 3D organization of keratin networks differs profoundly between different epithelia: for example, the simple epithelial cells lining the intestine contain a well-defined lateral and apical network, keratinocytes contain a dense 3D network encompassing the entire cytoplasm, and hepatocytes have a prominent submembraneous network ( Schwarz et al, 2015 ; Strnad et al, 2008 ). Network organization is furthermore affected by mechanical stress ( Beriault et al, 2012 ; Felder et al, 2008 ; Fois et al, 2013 ; Karsch et al, 2020 ; Lutz et al, 2020 ; Quinlan et al, 2017 ) and differentiation-status ( Coch and Leube, 2016 ; Iwatsuki and Suda, 2010 ; Leube et al, 2017 ; Quinlan et al, 2017 ; Tateishi et al, 2017 ). In addition, individual proteins such as Ndel1 and plectin have been shown to regulate keratin network organization ( Kim et al, 2021 ; Moch et al, 2016 ; Osmanagic-Myers et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%